2000
DOI: 10.1164/ajrccm.162.4.9909096
|View full text |Cite
|
Sign up to set email alerts
|

Association between Air Pollution and Lung Function Growth in Southern California Children

Abstract: Average growth of lung function over a 4-yr period, in three cohorts of southern California children who were in the fourth, seventh, or tenth grade in 1993, was modeled as a function of average exposure to ambient air pollutants. In the fourth-grade cohort, significant deficits in growth of lung function (FEV 1 , FVC, maximal midexpiratory flow [MMEF], and FEF 75 ) were associated with exposure to particles with aerodynamic diameter less than 10 m (PM 10 ), PM 2.5 , PM 10 -PM 2.5 , NO 2 , and inorganic acid v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
115
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 374 publications
(122 citation statements)
references
References 30 publications
(25 reference statements)
7
115
0
Order By: Relevance
“…These results therefore support recent cohort data in the USA demonstrating that exposure to pollution from traffic has adverse effects on children’s lung function development 2 16 17. Overall, there was a lack of association between air pollution and respiratory and allergic symptoms which is in agreement with two other studies that used subjective outcome data 18 19.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results therefore support recent cohort data in the USA demonstrating that exposure to pollution from traffic has adverse effects on children’s lung function development 2 16 17. Overall, there was a lack of association between air pollution and respiratory and allergic symptoms which is in agreement with two other studies that used subjective outcome data 18 19.…”
Section: Discussionsupporting
confidence: 90%
“…There are also studies demonstrating an association between traffic pollution and sensitisation to pollen and outdoor allergens, as well as increased levels of total and specific IgE 2 7 12. Data from cross-sectional studies have also suggested that ambient air pollution can affect lung function in 10-year-old children,1315 and recent longitudinal cohort data have shown that pollution from traffic has adverse effects on children’s lung development between 10 and 18 years of age 2 16 17. However, other studies have indicated no association between air pollution indicators and respiratory symptoms18 or lung function 19…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Air pollutant or particulate matter also causes inflammation/asthma and reduced lung function. Earlier studies have shown that outdoor air pollution is associated with decreased lung function [17,18]. Pollution and smoking can also cause cell death by necrosis, and with the process of apoptosis, which can increase inflammatory strength [19].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, since NO 2 is emitted in large quantities in automobile exhaust gas, NO 2 is often used as an indicator of traffic-related air pollution in urban areas [3]. In terms of its effect on human health, long-term NO 2 exposure can lead to respiratory depression and respiratory illness [4][5][6][7][8]. In addition, it is a precursor of aerosol nitrate, tropospheric ozone, and the hydroxyl radical (OH), the main atmospheric oxidant [9].…”
Section: Introductionmentioning
confidence: 99%